A New Acinetobacter Isolate Is an Extremely Efficient Biofilm-Formative Denitrifying Bacterium - Shelly, Yuval; Kuc, Martin E.; Iasur-Kruh, Lilach; Azerrad, Sara; Kurzbaum, Eyal (Frontiers in Environmental Science, 2020)
A very effective removal of nitrate in batch and continuous experiments was achieved by a newly biofilm-formative isolated bacterium, identified by 16S rRNA as Acinetobacter EMY. The anoxic denitrifying capabilities of Acinetobacter EMY, attached to high-density polyethylene biocarriers in batch and continuous moving bed bioreactors, demonstrated up to 1.75 times higher nitrate removal compared with a bacterial suspension. The denitrification rates of nitrate (200 mg/l) in the continuous operation mode were 0.39, 0.65, 1.23, and 1.14 kg-N/m3.d, with hydraulic retention times (HRTs) of 12, 8, 4, and 2 hours, respectively, whereas the batch reactor removal performance showed up to 1.49 kg-N/m3.d. Measurements of COD in both reactors indicated that the isolate exploits the entire amount of organic matter (700 mg/l COD) in the medium. To the best of our knowledge, these findings are the highest values obtained for nitrate removal in comparison to previous studies focused on the characterization of denitrifying isolates. The isolated bacterium therefore provides a good solution for biological treatment of nitrogen in water, particularly in treatment systems that integrate fixed biomass in the treatment process.